De atividades gamificadas ao Portlibras: Uma investigação sobre a criação de jogos para o ensino de português como L2 para surdos - Gonçalves, Angélica Rodrigues (2023)
This research was developed through a qualitativedescriptive case study, and was guided by the perspective of Applied Linguistics. Our objective was to analyze the creation and application of gamified activities, planned and designed to create a teachinglearning tool for Portuguese as a second language (L2) which suited the linguistic and psychosociocultural needs and specificities of the deaf. In this regard, we expected to understand whether the construction of these activities could contribute to the learning process and to a positive involvement of deaf users with the written modality of the Portuguese language as L2. It was also our intent to find out whether this tool could bring the deaf community closer to the teaching of Portuguese. Our methodology consisted of providing discussion spaces through Workshops specially developed so that participants could share reflections about a language learning experience based on a playful and gamified approach. All research data was then collected from these events. Data analyzes were supported by the theoretical background concerning aspects involved in the process of teachinglearning Portuguese as L2 to the deaf, as discussed by Quadros (1997), Skliar (2013), Brayner (2019), Lacerda (1998), among others. The reflective considerations about language learning, social and historical contexts and other subjects that contributed to the reflections described here were guided by authors such as Coracini (2008; 2003); Leffa (1999; 2014; 2020) and Vygotsky (1991). As for aspects related to the creation and design of games and gamification, we were guided by Huizinga (2000); Caillois (1990); Zichermann and Cunningham (2011); McGonigan (2011); Reinhardt (2019), and others. We aimed at analyzing our research data in its real circumstances of use, in practice, in applied use of the teaching approach proposed by the research, and from the perspective of collaborative, interactive and agile construction. To this end, we sought support in the theoretical framework of Sommerville (2011). Our analysis is based on the contributions of the research participants, deaf and hearing people who work with deaf people, graduated or in training, from different regions of the country and of different ages. We also took into consideration, for the analysis, the construction of the game design, the gamified activities and the participants' reactions in relation to these elements. The fact that the work was carried out in stages allowed us to understand relevant issues about the construction of an innovative and technological idea for teaching languages to the deaf, and this enabled us to observe important aspects that guide this construction. We can conclude, from the research results, that: a) deaf people, in many parts of our country, still face serious challenges regarding inclusion and accessibility, issues that need to be considered when creating language learning strategies, in the case of deaf students, especially concerning their second language; b) for the development of gamified activities, it is necessary to take into account the presence of the two languages involved, Portuguese and Libras, and of various semiotic elements, such as images, photos, colors, shapes and others; c) it is possible to bring deaf people closer to the teachinglearning process of Portuguese L2, through games and gamified activities which may provide playful, motivating and fun interactions; and d) the game created during our research still has a low score in relation to the RETAIN model, as proposed by Gunter (2008), and needs notable improvements. However, we believe that it is an initial game proposal, for teaching Portuguese as L2 for deaf people, which, according to that author's conceptions, still needs to be improved in relation to aspects such as game script, story, and other important aspects for a game of this kind.